INFORMATION CONTROL DESIGN HOUSE PROTOTYPE COMPUTER BASED IBM PC - Wahyu Hidayat; Drs. Lingga Hermanto, MM Drs. Lingga Hermanto, MM (Jurnal Sistem Komputer, 2002)
Computer systems today are not only used as a tool to assist their daily work, but alsoused as entertainment and advice on development control is currently used as a tool.That's why the house lights were used computers to control them. As in theconventional switch, the computer can control the lights manually through a pressurebutton. Besides computers have advantages in controlling the lights are programmed.So users need not bother to go to each room to turn on or turn off the lights in thebuilding with plenty of space. Simply through one central place, everything has beenchecked. So we use a relay that will mediate between the computer with a series oflights. So that each can operate can be mutually affected the voltage differencebetween the two.